Pendampingan Calon Guru Biologi dalam Merancang Penelitian Tindakan Kelas - Faisal Faisal; Sitti Saenab; Hartono Hartono; Irma Suryani Idris; Andi Rahmat Saleh (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2023)
The curriculum of the pre-service Teacher Professional Education program requires prospective teachers to implement Classroom Action Research during the Field Experience Program. The implementation of Classroom Action Research is expected to improve the quality of teaching and learning practices in schools by developing teachers' reflective attitude towards student learning. This Community Partnership Program aims to improve the understanding of Biology teacher candidates who are members of the Pre-service Teacher Professional Education program, Makassar State University, regarding the principles and methodology of Classroom Action Research. This program was carried out face-to-face and online (Zoom meeting) in March 2023 with 35 participants. Service activities are divided into three stages, namely program planning, implementation, and evaluation of achievement targets. The survey results at the beginning of the activity showed that most prospective Biology teachers still had limited experience with the implementation of Classroom Action Research. However, during the activity, participants were actively involved in discussing the topic of problems and solutions to learning problems at school, determining the learning cycle, and assessing student learning outcomes. At the end of the activity, prospective teachers were also able to make a Classroom Action Research plan.